Relationship marketing in customer loyalty of commercial galleries in times of Covid-19 - Cano Torres, Luz Mirella (2021)
The main objective of the study is to determine the level of dependence between relationship marketing and the level of customer loyalty to the brand. The study was conducted through a quantitative approach using the CAWI method. Relationships were determined by several factors. The loyalty factors are: Differentiation, Personalization, Satisfaction, Loyalty, usually. The relationship marketing indicators are: Trust, Commitment, Customer Satisfaction, Intention to renew the relationship. The survey results were processed using statistical methods. In particular, internal consistency checks performed on the questionnaire with questions to use Cronbach’s alpha. The use of such criteria allows to draw conclusions about the high level of consistency. The coefficient of determination was used for statistical verification of dependence. The results of the calculations confirmed a high level of dependence. Dependence was also confirmed by calculating p-values with a high level of probability. Conclusions were drawn according to the results of the empirical investigation.